Extracting Ability of Hydrophobic Eutectic Solvents for the Solvent Extraction of Molybdenum (Vi) and Rhenium (Vii) Without Third-Phase Formation in a Real Pregnant Leach Solution - Cabezas-Cornejo, R (Elsevier B.V., 2026)
The formation of a third phase in the solvent extraction (SX) of molybdenum (Mo) and rhenium (Re) is a significant concern in industry. The objective of this work was therefore to evaluate the extraction performance of two different hydrophobic eutectic solvents (HES) in the SX of Mo(VI) and Re(VII) from both synthetic and a real industrial pregnant leach solution (PLS) obtained from the leaching of Chilean molybdenite, as alternatives to commercial organic phases and to prevent third-phase formation. The HES employed were TOPO:DecA and [N8881][Cl]:DecA. Various operating parameters were analyzed to assess the extraction performance of both HES at different molar ratios, including the initial concentration of Mo(VI) in the PLS and the aqueous-to-organic (A/O) ratio. The results indicate that, in SX with both HES, no third-phase formation was observed even at high Mo(VI) concentrations and elevated A/O ratios. Moreover, all evaluated systems effectively and selectively extracted Mo(VI) and Re(VII) from both synthetic and real PLS, achieving high extraction percentages (%E ≈ 98 %), while impurities were not extracted. Using TOPO:DecA (1:1) in a real industrial PLS resulted in promising and selective extraction of Mo(VI) and Re(VII) with minimal impurity co-extraction. Five SX–stripping cycles were performed without a decrease in %E or alteration of the HES chemical structure. The results presented here highlight a promising and more sustainable alternative to commercial organic solvents, which could also represent an economically attractive option for the Mo(VI) and Re(VII) industry. © 2025 Elsevier B.V.